ANALISIS KONTEN DAKWAH FAHRUDDIN FAIZ DALAM PODCAST SPOTIFY - Hartono, Toni; Revan, Muhammad; Darmawati, Faras; Mildah; Nasution, Toni Pangidoan (Program Studi Komunikasi dan Penyiaran Islam, 2025)
The development of digital technology has driven significant transformations in various aspects of life, including in the way Islamic da'wah is delivered. Digital media such as podcasts are now a strategic alternative in reaching a wider audience, especially the younger generation who are familiar with digital audio platforms such as Spotify. This study aims to analyze the da'wah strategy carried out by Fahruddin Faiz in utilizing podcasts as a medium for spreading Islamic values. The study focuses on aspects of message content, delivery style, audience affordability, and its relevance to the spiritual needs of contemporary society. Through a qualitative approach with a content analysis method, this study examines three selected episodes of the Ngaji Filsafat podcast on Spotify. The results showed that Fahruddin Faiz packaged da'wah philosophically, reflectively, and communicatively with simple but profound language, making podcasts an inclusive, contemplative, and relevant da'wah space for modern society. Fahruddin Faiz's use of podcast media has proven to be an adaptive and contextual da'wah strategy in responding to the challenges of today's religious digitalization